Starts & Planets: Questions & answers - "Kerrod, Robin" (Kingfisher Publications: London., 2005)
Stars and Planets" is part of the comprehensive "Questions and Answers" series. The book contains information on stars, planets, galaxies, asteroids, meteorites and the solar system and discusses questions such as: How big are the stars? and How big is the solar system?
Keywords: General Science - Book